MUC1-C promotes the suppressive immune microenvironment in non-small cell lung cancer. (2nd September 2017) - Bouillez, Audrey; Adeegbe, Dennis; Jin, Caining; Hu, Xiufeng; Tagde, Ashujit; Alam, Maroof; Rajabi, Hasan; Wong, Kwok-Kin; Kufe, Donald
ABSTRACT: The cancer immune microenvironment is of importance for the effectiveness of immunotherapy; however, its dysregulation is poorly understood. The MUC1-C oncoprotein is aberrantly overexpressed in non-small cell lung cancer (NSCLC) and has been linked to the induction of PD-L1. The present work investigated the effects of targeting MUC1-C in an immuno-competent MUC1 transgenic (MUC1.Tg) mouse model. We show that Lewis Lung Carcinoma cells expressing MUC1-C (LLC/MUC1) exhibit upregulation of PD-L1 and suppression of interferon-γ (IFN-γ). In studies of LLC/MUC1 cells growing in vitro and as tumors in MUC1.Tg mice, treatment with the MUC1-C inhibitor, GO-203, was associated with the downregulation of PD-L1 and induction of IFN-γ. The results further demonstrate that targeting MUC1-C results in enhanced effector function of CD8+ tumor-infiltrating lymphocytes (TILs) as evidenced by increased expression of the activation marker CD69, the degranulation marker CD107α, and granzyme B. Notably, targeting MUC1-C was also associated with marked increases in TIL-mediated killing of LLC/MUC1 cells. Analysis of gene expression data sets further showed that overexpression of MUC1 in NSCLCs correlates negatively with CD8, IFNG and GZMB, and that decreases in CD8 and IFNG are associated with poor clinical outcomes. These findings in LLC/MUC1 tumors and in NSCLCs indicate that MUC1-C→PD-L1 signaling promotes the suppression of CD8+ T-cell activation and that MUC1-C is a potential target for reprogramming of the tumor microenvironment.